Pre-coordinated Deployment of Emergency Medical Team (Emt) Orthopaedic Spine Specialist-Cell: Experience in An Acute-Phase of the 2018 Lombok Earthquake by Yogyakarta Team - Gean Juniwan Syahputra Batong (Journal of Global Pharma Technology, 2016)
Indonesia is located at the meeting point of three major continental plate-the Pacific, the Eurasian, and the Indo-Australian plates-and also on the “Ring of fire”, which makes Indonesia vulnerable to earthquakes and volcanic eruption. As population density continues to increase, challenges grow for emergency responders in the aftermath of such disaster [1].Sudden Onset Disaster (SOD) occur with little or no warning and often cause excessive injuries far surpassing the national response capacities. Following SODs a large number of Medical Teams or Emergency Medical Teams often arrive in-country to provide emergency care to patients with traumatic injuries and other life-threatening injuries. Emergency Medical Teams are groups of health professionals (doctors, nurses, paramedics etc.) that treat patients affected by an emergency or disaster. Emergency Medical Teams, according to their capability, classified into 5 types; such as EMT-1 Mobile, EMT-1 fixed EMT-2, EMT-3, and EMT Specialized cell. Providing trauma care or medical care in disaster setting is very challenging. After an earthquake, local medical infrastructure was often damaged or destroyed, thus healthcare responders may not be able to rely on the medical resources of the afflicted region. Therefore, healthcare responders must provide the necessary medical equipment and supplies which requires good planning, efficient resource allocation, and understanding of the injuries that are likely to be encountered. Earthquake-related trauma results in severe injuries and requires rapid response in the acute-phase. Spinal injuries are important issue because the delay in adequate management can cause the patient to fall into a worse state, which can result in death or permanent disability. Orthopaedic spine surgeon on a disaster team could be an important asset during the response. The aim of this report was to evaluate whether the challenges faced in an acute-phase of earthquake can be obstacles to perform adequate orthopaedic spine management.